The Adventures of Kirby Allbee in Saul Bellow’s The Victim - Dr. Jamal Assadi (My University, 2012)
With the appearance of Ravelstein, Bellow’s most recent novel, we again encounter a familiar character in Chick, who, in more ways than one, functions as a “mentor”, a “brain truster”, a “reality instructor” or a “Machiavellian”, thereby indicating a trend and a tradition in Bellow’s fiction. Despite individual differences, these figures are often presented as actors replete with constantly changing situations, schemes, plots strategies and roles, who through the power of words, try to reinterpret reality and to convince themselves and others to accept their revision of it. However, it is in the nature of such characters to pretend they are good actors; each endorses a conception of life that relies on a strong belief confirming that there are solid systems, rules, codes and values that underlie all social and cultural practices. One of the pioneers of such figures is Kirby Allbee, whose conduct (associated with strong sense of acting) savours of possession and exorcism.
He is both a Jinni who haunts the soul of Asa Leventhal, the protagonist of the novel, and, in consequence, accelerates his deterioration and confusion, and paradoxically the exorcist who helps Asa regain his spirit and expel the devil. While this paper closely examines the roles of Kirby Allbee, his impact on Asa Leventhal and on the narrative aspect, it aims to present Allbee as a typical representative of such figures and, hence, to call for a deeper examination of the tradition.

With the appearance of Ravelstein, Bellow’s most recent novel, we again encounter a familiar character in Chick, who, in more ways than one, functions as a “mentor”, a “brain truster”, a “reality instructor” or a “Machiavellian”, thereby indicating a trend and a tradition in Bellow’s fiction. Despite individual differences, these figures are often presented as actors replete with constantly changing situations, schemes, plots strategies and roles, who through the power of words, try to reinterpret reality and to convince themselves and others to accept their revision of it. However, it is in the nature of such characters to pretend they are good actors; each endorses a conception of life that relies on a strong belief confirming that there are solid systems, rules, codes and values that underlie all social and cultural practices. One of the pioneers of such figures is Kirby Allbee, whose conduct (associated with strong sense of acting) savours of possession and exorcism.
He is both a Jinni who haunts the soul of Asa Leventhal, the protagonist of the novel, and, in consequence, accelerates his deterioration and confusion, and paradoxically the exorcist who helps Asa regain his spirit and expel the devil. While this paper closely examines the roles of Kirby Allbee, his impact on Asa Leventhal and on the narrative aspect, it aims to present Allbee as a typical representative of such figures and, hence, to call for a deeper examination of the tradition.
The Adventures of Kirby Allbee in Saul Bellow’s The Victim